2021
DOI: 10.1186/s41983-021-00276-6
|View full text |Cite
|
Sign up to set email alerts
|

Spheno-orbital meningiomas: surgical techniques and results

Abstract: Introduction Spheno-orbital meningiomas are characterized by bone invasion with extensive hyperostosis and possible encroachment into the orbit, infra-temporal fossa, and/or the cavernous sinus that render total surgical excision challenging. The surgical technique utilized is a key factor facilitating complete resection and hence improvement of proptosis and accompanying visual symptoms. Methods This is a retrospective study of twenty-two patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Spheno-orbital meningiomas are diagnosed based on their growth pattern and their radiographic appearance but not on their histological morphology. They tend to induce bone hyperostosis and the extent of hyperostosis is usually disproportionate to the size of the meningioma [27], [28]. In this study, there a recurrence of four subjects in Grade I meningioma and one subject in Grade III meningioma.…”
Section: Discussionmentioning
confidence: 46%
“…Spheno-orbital meningiomas are diagnosed based on their growth pattern and their radiographic appearance but not on their histological morphology. They tend to induce bone hyperostosis and the extent of hyperostosis is usually disproportionate to the size of the meningioma [27], [28]. In this study, there a recurrence of four subjects in Grade I meningioma and one subject in Grade III meningioma.…”
Section: Discussionmentioning
confidence: 46%
“…Open approaches provide a wider exposure to tumor tissue; however, they may be associated with functional and cosmetic post-operative complications, which can be avoided in minimally invasive techniques [ 12 , 15 ]. To date, there remains no consensus surrounding the reconstruction of orbital walls following tumor resection, with proponents of bony construction deeming it a necessity to reduce the occurrence pulsatile exophthalmos [ 16 ]. A recent meta-analysis found that the pterional approach relieves visual symptoms including diplopia, ophthalmoplegia, and visual acuity and field deficits in approximately 90% of patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,[11][12][13][14] Frontolateral and FTOZ approaches are also recommended. 11,12,15 The latter is a modification of the classic pterional approach that increases surgical exposure to the orbit and decreases the need for brain retraction. 11 Based on our surgical experience and aiming at restoring the cosmetic and functional abilities of the patients, we preferred to use FTOZ in all patients.…”
Section: Discussionmentioning
confidence: 99%